Prostaglandin F2α-Induced Functional Regression of the Corpus Luteum and Apoptosis in Rodents - Zhiyan Wang (Journal of Pharmacological Sciences, 2003)
We investigated the relationship between prostaglandin (PG) F2α-induced functional luteal regression and apoptosis in the rodent ovary. Administration of PGF2α significantly decreased the serum levels of progesterone within 12 h after treatment in pseudopregnant mice. Apparent signals were detected in luteal tissues at 24 to 72 h by terminal deoxynucleotidyl transferase (TdT)-mediated dUTP-biotin nick endo labeling (TUNEL) assay. PGF2α significantly increased the levels of the cleavage nuclear poly (ADP-ribose) polymerase fragment and transforming growth factor-β (TGF-β) mRNA within 48 h. PGF2α (10 μM) decreased progesterone secretion 6 to 72 h after its addition in luteinized ovarian cells, whereas C2-ceramide (25 μM) decreased progesterone levels by 44% 72 h after its addition. DNA fragmentation was not observed in the cultured cells treated with PGF2α for 24 h, although cells incubated with C2-ceramide showed fragmentation. Treatment with PGF2α for 1 h caused a distinct decrease in luteinizing hormone (LH)-induced cyclic AMP production. Thus, the inhibitory effect of PGF2α on progesterone secretion may be caused by both the blockage of the functional LH receptor and the activation of apoptotic signaling.